(untitled) (Web of Teachers: Inderscience Research, 2026)
Engineering Computer Graphics (ECG) is a critical discipline in modern higher education, enabling students to design and model processes digitally in fields such as manufacturing, architecture, and industrial design. This study examines pedagogical methods and software tools, including AutoCAD, ArchiCAD, and 3ds Max, to enhance students’ spatial reasoning, technical thinking, and creative competencies. Integrating modern ICT and aesthetic approaches in ECG education improves learning outcomes and prepares competitive, skilled specialists for contemporary engineering challenges.